Systemic and Lung Inflammation and Oxidative Stress Associated With Behavioral Changes Induced by Inhaled Paraquat Are Ameliorated by Carvacrol - Arghavan Memarzia; Fatemeh Amin; Amin Mokhtari-Zaer; Zohre Arab; Saeideh Saadat; Mahrokh Heydari; Zahra Ghasemi; Farzaneh Naghdi; Mahmoud Hosseini; Mohammad Hossein Boskabady (PPAR Research)
Paraquat (PQ) is an herbicide toxin that induces injury in different organs. The anti-inflammatory and antioxidant effects of carvacrol were reported previously. The effects of carvacrol and pioglitazone (Pio) alone and their combination on inhaled PQ-induced systemic and lung oxidative stress and inflammation as well as behavioral changes were examined in rats. In this study, animals were exposed to saline (control [Ctrl]) or PQ (PQ groups) aerosols. PQ-exposed animals were treated with 0.03 mg/kg/day dexamethasone (Dexa), 20 and 80 mg/kg/day carvacrol (C-L and C-H), 5 mg/kg/day Pio, and Pio+C-L for 16 days. Inhaled PQ markedly enhanced total and differential white blood cell (WBC) counts, nitric oxide (NO), and malondialdehyde (MDA) levels but decreased catalase (CAT) and superoxide dismutase (SOD) activities and thiol levels both in the bronchoalveolar lavage fluid (BALF) and blood and increased interferon-gamma (INF-γ) and interleukin-10 (IL-10) levels in the BALF (p<0.001 for all cases) except lymphocyte count in blood which was not significantly changed. The escape latency and traveled distance were increased in the PQ group. However, the time spent in the target quadrant in the Morris water maze (MWM) test and the duration of time latency in the dark room in the shuttle box test were reduced after receiving an electrical shock (p<0.05–p<0.001). Inhaled PQ-induced changes were significantly improved in carvacrol, Pio, Dexa, and especially in the combination of the Pio+C-L treated groups (p<0.05–p<0.001). Carvacrol and Pio improved PQ-induced changes similar to Dexa, but ameliorative effects produced by combination treatments of Pio+C-L were more prominent than Pio and C-L alone, suggesting a potentiating effect for the combination of the two agents.